Предмет: Алгебра,
автор: daschatatarova
помогите, пожалуйста, с номером 4.33
Приложения:
![](https://files.topotvet.com/i/a02/a02735ccaf54914ff1c0384fb8ecb6b1.jpg)
Ответы
Автор ответа:
0
a/(a²-1) + (a²+a-1) / (a³-a²+a-1) + (a²-a-1) / (a³+a²+a+1) - 2a³/ ((a²-1)(a²+1)) =
= a/(a-1)(a+1) + (a²+a-1)/(a²(a-1)+(a-1)) + (a²-a-1)/(a²(a+1)+(a+1)) - 2a³/((a²-1)(a²+1)) = a/(a-1)(a+1) + (a²+a-1)/(a²+1)(a-1) + (a²-a-1)/(a²+1)(a+1) - 2a³/((a²-1)(a²+1)) =
= a(a²+1)(a²-1)+(a²+a-1)(a²-1)(a+1)+(a²-a-1)(a²-1)(a-1)-2a³(a²-1) /
/ (a²+1)(a²-1)(a-1)(a+1) =
= a(a²+1)+(a²+a-1)(a+1)+(a²-a-1)(a-1)-2a³ / (a²+1)(a²-1) =
= a³+a+a³+a²+a²+a-a-1+a³-a²-a²+a-a+1-2a³ / (a²+1)(a²-1) =
= (a³+a) / (a²+1)(a²-1) =
= a(a²+1) / (a²+1)(a²-1) = a/(a²-1)
при a=3/2 3/2 : (9/4 -1) = 3/2 × 4/5 = 6/5 = 1,2
= a/(a-1)(a+1) + (a²+a-1)/(a²(a-1)+(a-1)) + (a²-a-1)/(a²(a+1)+(a+1)) - 2a³/((a²-1)(a²+1)) = a/(a-1)(a+1) + (a²+a-1)/(a²+1)(a-1) + (a²-a-1)/(a²+1)(a+1) - 2a³/((a²-1)(a²+1)) =
= a(a²+1)(a²-1)+(a²+a-1)(a²-1)(a+1)+(a²-a-1)(a²-1)(a-1)-2a³(a²-1) /
/ (a²+1)(a²-1)(a-1)(a+1) =
= a(a²+1)+(a²+a-1)(a+1)+(a²-a-1)(a-1)-2a³ / (a²+1)(a²-1) =
= a³+a+a³+a²+a²+a-a-1+a³-a²-a²+a-a+1-2a³ / (a²+1)(a²-1) =
= (a³+a) / (a²+1)(a²-1) =
= a(a²+1) / (a²+1)(a²-1) = a/(a²-1)
при a=3/2 3/2 : (9/4 -1) = 3/2 × 4/5 = 6/5 = 1,2
Автор ответа:
0
Привет из Мурманска...)))
Автор ответа:
0
спасибо большое за решение)))
Похожие вопросы
Предмет: ОБЖ,
автор: BitchVKooK
Предмет: Русский язык,
автор: Lilanero
Предмет: Математика,
автор: m892190e
Предмет: История,
автор: alievkamran
Предмет: Физика,
автор: sea2000